2015
DOI: 10.2967/jnumed.114.146688
|View full text |Cite
|
Sign up to set email alerts
|

Optical In Vivo Imaging of the Alarmin S100A9 in Tumor Lesions Allows for Estimation of the Individual Malignant Potential by Evaluation of Tumor–Host Cell Interaction

Abstract: Tumors recruit and reprogram immune cells to support tumor development and spread, the most prominent among them being of monocytic origin such as tumor-associated macrophages (TAM) or myeloid-derived suppressor cells (MDSC). The alarmin S100A8/ A9 has been implicated in the induction of TAM and MDSC. We assessed S100A9 as a molecular imaging marker for the activity of tumor-associated immune cells in a syngeneic murine breast cancer model. S100A9 could serve as a surrogate marker for tumor immune crosstalk as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 42 publications
0
24
0
Order By: Relevance
“…The biological effects of S100A8/A9 depend on the extra- or intracellular localization of the protein complex. Likely released by infiltrating polymorphonuclear leukocytes, macrophages [ 13 , 14 ], and by epithelial cells, extracellular S100A8/A9 in the tumor microenvironment is associated with inflammation-induced tumor progression [ 15 ] and may serve as a prognostic marker in some types of cancer [ 16 , 17 ]. For example, S100A8/A9 is often abnormally elevated in tumors originating in tissues that are negative for the protein complex, whereas intracellular levels decrease in tumors such as HNSCC that originate from tissues with constitutive expression [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…The biological effects of S100A8/A9 depend on the extra- or intracellular localization of the protein complex. Likely released by infiltrating polymorphonuclear leukocytes, macrophages [ 13 , 14 ], and by epithelial cells, extracellular S100A8/A9 in the tumor microenvironment is associated with inflammation-induced tumor progression [ 15 ] and may serve as a prognostic marker in some types of cancer [ 16 , 17 ]. For example, S100A8/A9 is often abnormally elevated in tumors originating in tissues that are negative for the protein complex, whereas intracellular levels decrease in tumors such as HNSCC that originate from tissues with constitutive expression [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several different cells including various tumor cells and immune cells have been reported as potential producers and providers of S100A8/A9 and this can also be found in the tumor microenvironment as well as in premetastatic tissue. For the experimental model we have been using, we could however exclude tumor cells as the source of S100A8/A9, by analysis of cell lysates and tissue culture supernatants, and by FACS of harvested tumor tissue, showing virtually all S100A9 + cells in the 4T1.2 model, to be CD11b + 15. Metastatic breast cancer is known to secrete CCL2 39, which can stimulate MDSC-like and trigger S100A8/A9 release (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…We recently established target-specific in vivo S100A8/A9 optical imaging for monitoring of monocyte activity in local inflammation 14 and primary cancer lesions 15, using fluorescence-labeled antibodies. The local S100A8/A9-release correlated with the accumulation of tumour-associated CD11b + cells and proved predictive of tumor development.…”
Section: Introductionmentioning
confidence: 99%
“…It will promote the circulating breast tumor cells to seed the lung. Becker A also reported that S100A8 has been implicated in the induction of tumor associated macrophaged (TAM) or myeloid-derived suppressor cells (MDSC), which support tumor development and spread [35]. Also there are increasing studies showed the signaling pathways of S100A8 in breast cancer, such as p38-MAPK, IL6 -JAK2-STAT3 [36] and so on.…”
Section: Figure 1 Expression Of Jab1 and S100a8 Proteins In Breast Camentioning
confidence: 99%